Jakten på det kompetenta barnet - Emilsson, Anette; Pramling Samuelsson, Ingrid (Nordisk barnehageforskning, 2012)
Title: Looking for the competent child Abstract: From different documentation situation the aim of this study is to investigate the focus of the documentation as well as the communication between preschool teachers and children in these situations. The research questions are: What is the focus of the documentation? What characterizes the communication between the teachers and the children when these teachers at the same time are documenting? To interpret and understand this communication Habermas’ concepts of communicative and strategic action are used. Data consists of video observations, where 157 minutes of recordings have been analyzed. 30 children, 1–3 years, and their 7 preschool teachers have participated in the study. The results show that it is mainly children’s achievements that are documented and that the preschool teachers either become silent observers or eager advocators of a particular discovery. What is communicated and documented by the teachers have a high degree of abstraction, and the communication is of a strategic character.